Hepatic artery lymph node relevance in periampullary tumors: A retrospective analysis of survival outcomes - Conde, Danny; Rey, Carlos; Pardo, Manuel; Recaman, Andrea; Sabogal Olarte, Juan Carlos (Frontiers in Surgery, 2022)
Background The Periampullary area comprehends a heterogeneous and complex structure with different histological tissues. Surgical standards include the peripancreatic regional lymphadenectomy, and during pancreatoduodenectomy (PD) the hepatic artery lymph node HALN(8a) is dissected. We aimed to describe the prognostic significance of the HALN(8a) lymph node metastasis in terms of disease-free survival (DFS) and overall survival (OS) in a specific cohort of patients in limited economic and social conditions. Methods A retrospective study was conducted based on a prospective database from the HPB department of patients who underwent pancreaticoduodenectomy (PD) due to periampullary tumors during 2014 - 2021. Overall survival (OS) and disease-free survival (DFS) were estimated to be associated with positive HALN(8a) using Kaplan-Meier analysis. Log Rank test and Cox proportional hazards regression analysis was used. Results 111 patients were included, 55,4% female. The most frequent pathology was ductal adenocarcinoma (60.3%). The positive rate of the HALN(8a) node was 21.62%. The Median OS time was 25.5 months, and the median DFS time was 13,8 months. Positive HLAN(8a) node, the cutoff of lymph node ratio resection (LNRR), and vascular invasion showed a strong association with OS. (CoxRegression p = 0.03 HR 0.5, p 0.003 HR = 1.8, p = 0.02 HR 0.4 CI 95%). In terms of DFS, lymph node ratio cutoff, tumoral size, and vascular invasion showed a statistically significant association with the outcome (p = 0.008, HR = 1.5; p= 0.04 HR=2.1; p=0.02 HR=0.4 CI 95%). Conclusion In this series of PD, OS was reduced in patients with HALN(8a) compromise in patients with pancreatic cancer, however without statistical significance in DFS. In multivariate analysis, lymph node status remains an independent predictor of OS and DFS. Further studies are needed.